Efektivitas Intervensi Fisioterapi dalam Mengurangi Nyeri dan Meningkatkan ROM pada Lansia Penderita Osteoarthtritis Genu di RST. Soedjono Magelang - Zain, Siti Azzura; Razzaq, Aliyah Nadhifah; Indraprastha, Annya Shakty; Salsabila, Anida Nasywa; Septian Tri Wicaksono; Arjuna Fatkhur Roziq Pahlavi; Arif Pristianto; Munawar Munawar (Lembaga Pengembangan Kinerja Dosen, 2025)
Background: Knee osteoarthritis is one of the most common degenerative conditions in older adults, often causing pain and limited range of motion (ROM), which negatively affects quality of life. Physiotherapy management plays an important role in reducing pain, improving flexibility, and maintaining joint function. Objective: This study aims to evaluate the effectiveness of physiotherapy interventions in reducing pain and improving ROM in elderly patients with knee osteoarthritis. Method: A case study was conducted on a 63-year-old patient at Dr. Soedjono Level II Hospital, Magelang, who underwent three therapy sessions consisting of Infrared (IR), Transcutaneous Electrical Nerve Stimulation (TENS), Proprioceptive Neuromuscular Facilitation (PNF) with the hold-relax technique, and static cycling. Assessments were carried out using the Numeric Rating Scale (NRS), Likert Gait Scale (LGS), and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Results: The findings showed a significant reduction in pain on palpation (from 4/10 to 1/10), improvement in knee flexion ROM (from 110° to 135°), and functional enhancement indicated by a decrease in WOMAC scores from 39.58% to 27.08%. Conclusion: These results suggest that structured physiotherapy interventions provide therapeutic benefits in reducing pain, improving joint flexibility, and enhancing functional ability in elderly patients with knee osteoarthritis.